Levels of physical activity, barriers, and stage of change in an urban population from a municipality in Colombia (2011)
ABSTRACT: Objective: To assess the levels of physical activity, barriers, and stage of change in an urban population 25 to 50 years of age from the Municipality of Santa Rosa de Osos, department of Antioquia. Materials and methods: A prevalence study was conducted, with a two-stage random sampling among 357 individuals not suffering from any known cardiovascular disease. A pre-designed survey was conducted to assess the levels of physical activity, the stage of change, and physical activity barriers. Results: The total low physical activity was 9%, and by domains: work 66.9%, transport 60.8%, household and garden (yard work) 44.8%, and leisure-time 76.2%. The most important physical activity barriers were «lack of willpower» (70%) and «lack of time» (46.2%). The most prevalent stages of change were «contemplation» (40.3%) and «preparation» (17.1%). Conclusion: low physical activity levels were found in different domains of daily life, together with a high prevalence of barriers and stages prior to physical activity practice, mainly among women and obese subjects.